2022
DOI: 10.1108/ejm-03-2020-0214
|View full text |Cite
|
Sign up to set email alerts
|

“I’m hatin’ it”! Negative consumer–brand relationships in online anti-brand communities

Abstract: Purpose This paper aims to provide a better understanding of negative consumer–brand relationships in social-media-based anti-brand communities from a consumer culture theory (CCT) perspective. In particular, it investigates the purpose and the meaning of the consumer participation in online anti-brand communities, also through the analysis of the ways in which they express negative feelings toward the hated brands. Design/methodology/approach This study applies a “symbolic netnographic” method to six anti-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 96 publications
(216 reference statements)
0
24
0
Order By: Relevance
“…Banerjee and Goel (2020) have established that consumers hate a brand that is corporately irresponsible based on nonalignment of ethical values, legal and societal concerns. Previous studies have proven a positive impact of ideological incompatibility and BH in extant BH literature (Brandão and Popoli, 2022;Bryson et al, 2021;Curina et al, 2021;Lopez, 2021) albeit not in the arts marketing literature. Therefore, we hypothesized that: H2.…”
Section: Hypotheses Developmentmentioning
confidence: 95%
“…Banerjee and Goel (2020) have established that consumers hate a brand that is corporately irresponsible based on nonalignment of ethical values, legal and societal concerns. Previous studies have proven a positive impact of ideological incompatibility and BH in extant BH literature (Brandão and Popoli, 2022;Bryson et al, 2021;Curina et al, 2021;Lopez, 2021) albeit not in the arts marketing literature. Therefore, we hypothesized that: H2.…”
Section: Hypotheses Developmentmentioning
confidence: 95%
“…Moreover, several studies have shown the impact of brand anthropomorphism on positive consumer–brand relationships (Golossenko et al , 2020; Portal et al , 2018), whereas, to the best knowledge of the authors, there are no studies on the impact of the brand anthropomorphism on negative consumer–brand relationships. The pertinence for this topic was claimed in a very recent investigation (Brandão and Popoli, 2022).…”
Section: Introductionmentioning
confidence: 91%
“…From a self-focused perspective , brand anthropomorphism also includes perceived congruity between the brand and the self and brand-self connections (Attiq et al , 2022; Guido and Peluso, 2015; MacInnis and Folkes, 2017; Puzakova et al , 2009). When consumers anthropomorphize a brand, a schema for the type of person is suggested and, therefore, people evaluate it considering how well the brand’s features fit that schema (Aggarwal and McGill, 2007; Brandão and Popoli, 2022). In fact, believing in a nonhuman agent as having a human-like mind may result in the following: perceiving them as worthy of moral concern; perceiving them as capable of intentional action, translating into responsibility for them; and perceiving them as a source of normative social influence for the consumer (Waytz et al , 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, how negative emotions such as regret, shame or hate may influence CEBs in relational services requires empirical investigation. For instance, research suggests that negative emotions may lead to vindictive behaviors such as negative WOM and customers joining antibrand communities, which can destroy the image and reputation of a firm/brand (Brandão and Popoli, 2022). In a health care context, patients may also feel other negative emotions such as anxiety, depression and a loss of control (Kim, 2019), which may adversely affect their engagement behaviors.…”
Section: Limitations and Future Researchmentioning
confidence: 99%